A233 VEDOLIZUMAB FOR STEROID & INFLIXIMAB-REFRACTORY ICI-COLITIS. (26th February 2020) - Klemm, N K; Trasolini, R; Chahal, D; Donnellan, F
Abstract: Background: Immune checkpoint inhibitors (ICI), such as anti-PD1, improve survival in melanoma, renal carcinoma and prostate cancer. However, by disinhibiting the immune system, these treatments cause significant immune-related adverse events (irAE), including colitis. For ICI-colitis, guidelines suggest escalating from observation to steroids to infliximab, without strong evidence for additional options should these fail. Vedolizumab has been used in a small number of cases for steroid-refractory or dependent ICI-colitis; only 9 cases have been reported in patients who failed infliximab therapy with a response rate of 67%. Aims: To discuss a case of ICI-colitis that failed multiple steroid courses and infliximab infusions, but achieved remission with vedolizumab. Methods: A 65-year-old male with malignant melanoma was randomized to adjuvant nivolumab +/- ipilimumab and developed non-bloody diarrhea. Despite loperamide, diarrhea worsened to 4–5 bowel movements daily. Stool cultures and C. diff were negative and 85mg of daily prednisone was started, while the ICI was held for 8 weeks. After a 2nd steroid taper, diarrhea recurred and the patient received 2 infliximab infusions 18 days apart. Despite initial improvement, biopsies demonstrated colitis and he underwent a 3rd infusion with little response. Clinical and biopsy-confirmed remission was only achieved once 2 vedolizumab infusions were given. Results: Colitis is the most common ICI irAE, ranging in severity from mild to perforation and death. The incidence of grade 3 and 4 colitis, which require ICI discontinuation, is 1.3% for anti-PD1 and 13.6% in combination therapy. The severity of irAE is positively correlated with malignancy response and stopping ICI risks recurrence. Those that fail irAE medical management may require surgery. Thus, there is an impetus to continue the ICI and provide effective medical management for irAE. ICI-colitis guidelines are based on the CTCAE diarrhea classification and suggest supportive management and ICI continuation for grade 1. For grade 2, the ICI is held and steroids are started; infliximab is added for grades 3 and 4. However, 33–66% of patients are steroid-refractory or dependent; and patients may be infliximab non-responders, or unable to tolerate systemic side effects. Vedolizumab, an anti-α 4β 7-integrin, acts locally to inhibit T cells in the bowel wall, reducing inflammation in IBD. Recent reports, including ours, suggest usefulness in steroid and infliximab-refractory ICI colitis after only 2–4 infusions. When the inflammatory burden is high, the response rate is >80% and given its gut-specificity, side effects are minimal compared to infliximab. Although further evaluation is required, using vedolizumab as second-line therapy is reasonable. Conclusions: Given vedolizumab's safety and gut-specificity, it should readily be considered in the treatment of ICI irAE. Funding Agencies: None